A interação entre a responsabilidade social corporativa e a percepção de benefício, de preço e de valor e seu impacto de compra: um estudo em Uberlândia-MG - Bergson, Aline Martins (2011)
In recent decades companies and consumers have proven to be more engaged and willing to seek ways to combine the role with the economic and social environment. Many companies have moved to the issue of corporate social responsibility (CSR) and structured projects for a socially responsible management, investing in the moral relationship, transparent and quality to all its stakeholders. This dissertation examined the interaction between corporate social responsibility and the perception of benefit, price and value and its impact on purchase intent. Through the use of scenarios aimed to investigate whether the benefit and value perceived by the consumer in the offer of a company considered socially responsible justify a price above practiced by their competitors and influence purchase intent. To find the answer, questionnaires were filled in Uberlândia - MG, with two groups of respondents, making reference to the project turns Algar, implemented by an organization well known in the city, the Algar Group. The theoretical framework developed on the theme was developed from an analysis of studies on CSR and consumer behavior made in decades. The results showed that consumers surveyed perceive a benefit and a higher value in the supply of socially responsible company and are willing to pay 10% more for your product, just judging this price differential charged. The results also showed that the benefit of consumers surveyed understood the company's offer and the perception that the price differential has just related to the perception of consumers about the value of the company's offer and the perceived value that is related to purchase intent of consumers.